Association Between Body Mass Index and Outcomes in Venoarterial Extracorporeal Membrane Oxygenation. (February 2022) - Lu, Shu Yang; Ortoleva, Jamel; Colon, Katia; Mueller, Ariel; Laflam, Andrew; Shelton, Kenneth; Dalia, Adam A.
Abstract : BACKGROUND: The association between obesity, or elevated body mass index (BMI), and outcomes in patients receiving venoarterial extracorporeal membrane oxygenation (VA-ECMO) has not been well established. Recent studies in patients receiving venovenous ECMO did not detect an association between obesity and increased mortality. The purpose of this retrospective observational study is to evaluate the association between BMI and survival in patients receiving VA-ECMO for cardiogenic shock. METHODS: All patients >18 years of age supported on VA-ECMO for refractory cardiogenic shock in a single academic center between 2009 and 2019 were included. ECMO outcomes, including successful ECMO decannulation and 30-day survival, were analyzed after stratification according to BMI. Multivariable and univariate logistic regression were used to assess the association between BMI and VA-ECMO outcomes. RESULTS: Of the total patients (n = 355) cannulated for VA-ECMO, 61.7% of the patients survived to ECMO recovery/decannulation, 45.5% of the patients survived to 30 days after ECMO decannulation, and 38.9% of the patients survived to hospital discharge with no statistically significant differences among the BMI groups. Multivariable logistic regression did not reveal any associations between obesity as defined by BMI and survival to ECMO decannulation (odds ratio [OR] 1.07 per 5 unit increase in BMI, 95% confidence interval [CI], 0.86–1.33; P = .57), 30-day survival (OR = 0.91, 95% CI, 0.73–1.14; P = .41) or survival to hospital discharge (OR = 0.95, 95% CI, 0.75–1.20; P = .66). CONCLUSIONS: Despite potential challenges to cannulation and maintaining adequate flow during ECMO, this single centered, retrospective observational study did not detect association between BMI and survival to ECMO decannulation, 30-day survival, or survival to hospital discharge for patients requiring VA-ECMO for refractory cardiogenic shock. These data suggest that obesity alone should not exclude candidacy for VA-ECMO. The primary outcome in this retrospective study was survival of the ECMO therapy (survival to ECMO decannulation), defined as surviving >24 hours after decannulation without a withdrawal of care. Secondary outcomes included survival at 30 days and survival to hospital discharge.